Implementation of The Wadi'ah and Mudharabah Agreement on BTM Sang Surya Pamekasan in Increasing The Interest of MSME's Actors - Argantara, Zaid Raya; Muhajir, Ahmad (Universitas Islam Negeri Alauddin Makassar, 2023)
The existence of funding products at BTM Sang Surya Pamekasan serves as a means of collecting funds from the community which can then be distributed back to the community or UMKM actors who carry out productive economic activities. This funding product uses wadi’ah and mudharabah contracts. The purpose oh this analize is to find out how the implementation of the wadi’ah and mudharabah contracts in BTM Sang Surya Pamekasan in increasing the interest of UMKM actors and what are the obstacles faced by BTM Sang Surya Pamekasan increasing the interest of UMKM actors. This research uses descriptive qualitative methods, data sourced from observation, interviews and documentation. The results of this study explain that the wadi’ah and mudharabah contracts in BTM Sang Surya are applied to funding products, namely wadi’ah futures, wadi’ah savings and mudharabah savings while for the types of contracts used using Wadi’ah yad Al-Amanah, Wadi’ah yad Al-Amanah and Mudharabah mutlaqah. The efforts made by BTM Sang Surya to increase the interest of UMKM actors are carried out using three ways, namely fostering good relationships, lobying to customers then the last one always maintains customer trust in BTM Sang Surya Pamekasan. The obstacles faced by BTM Sang Surya are the increasing number of withdrawals at the same time, weak understanding of digital transactions, and the lack of nominal savings with ball pick-up facilities. Keyword: Implementation, Contract, UMKM